Developing Marine and Coastal-based Sport Tourism on the Waterfront: The Case of Manado Waterfront, Indonesia - Lagarense, Bet El Silisna; Walansendow, Agustinus (Graduate School, Universitas Brawijaya, 2016)
There are many marine-based sports that have become universally popular as tourist attraction on waterfronts. This study aimed to examine the existence of marine and coastal-based sport tourism on the waterfront. They are dependent on certain types of coastal environment or condition including surfing, windsurfing, fishing, scuba diving, snorkeling, water-skiing and sailing and parasailing. Each of these activities has millions of regular participants. Tourism communities realize the value of marine sports attached to waterfront and marine sport events continue to grow in size and number. This study uses on-site observation and interviews to the people at and around Manado waterfront. The results show that a number of benefits can be realized by communities of all sizes that have developed a strategic marine sports tourism plan such as 1) economic development for the city with increased benefits to host community and to the city in general; 2) marine sports system development by hosting events that are strategically planned leading to increased capacity within the city's marine sport system; 3) social and community development with trained volunteers increases community pride and the opportunity to enrich facility infrastructure. The community needs to be well equipped with a high standard of knowledge, skills and attitude to be employed in marine sports tourism sectors. Keywords: marine and coastal-based sport tourism, waterfront.